LITERATURE REVIEW: PENGARUH AEROBIC EXERCISE DAN WEIGHT TRAINING AEROBIC UNTUK MENINGKATKAN FLEXIBILITY HAMSTRING PADA CALON JAMAAH HAJI - Nala Tsaniyah Hendrawan (2020)
Objective: Decreased hamstring flexibility is influenced by increasing age, especially on prospective pilgrims who average age 51-60 years with the elderly category. This study aims to examine the literature research results with the topic of the influence of aerobic exercise and aerobic weight training to improve hamstring flexibility in prospective pilgrims. Method: Search for sources of literature research results in several databases such as Google Scholar, Science Direct, Elsevier, PEDro, PubMed by using certain keywords in the period 2012-2020. From the search results, 23 articles were obtained and only 14 articles met the source inclusion criteria. The methodological quality assessment of 14 articles was assessed using the Scimago Journal & Country Rank (SJR). Analysis of 14 journals was carried out based on the suitability of the topic, objectives, the research methods used, subject, interventions, instruments/parameters, and the results of each article. Results: After reviewing the literature as many as 14 articles showed that aerobic exercise and aerobic weight training with the type of eccentric exercise is effective for increasing hamstring flexibility. Conclusion: The results of the literature review of 14 articles that have been reviewed show that the intervention of aerobic exercise and weight training can increase the flexibility of hamstring in pilgrims.